2019
DOI: 10.1111/tmi.13317
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of norovirus and rotavirus co‐infection in children with acute gastroenteritis hospitalised in Brazzaville, Republic of Congo

Abstract: objective To evaluate the clinical severity of diarrhoea associated to viral co-infection in children with acute gastroenteritis.methods About 461 children under five years hospitalised with acute diarrhoea (266 males and 187 females) were enrolled in the study. Using stool samples, rotavirus and adenovirus infections were investigated by ELISA, and norovirus infections by nested duplex RT-PCR. We assessed social, demographic, clinical and behavioural conditions that might influence the occurrence of rotavirus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
2
3
0
Order By: Relevance
“…In the current study, the co-infection of rotavirus and norovirus was found to be 5.0%, which was higher than some previous studies [ 16 , 39 ]. The distribution of these co-infection cases was similar to that of either norovirus or rotavirus in terms of age and seasonality, which is consistent with data reported by Mikounou Louya et al [ 40 ]. The yearly co-infection rate showed a significant steady decrease during the study years, which may be related to the decreasing regional detection rate of rotavirus.…”
Section: Discussionsupporting
confidence: 90%
“…In the current study, the co-infection of rotavirus and norovirus was found to be 5.0%, which was higher than some previous studies [ 16 , 39 ]. The distribution of these co-infection cases was similar to that of either norovirus or rotavirus in terms of age and seasonality, which is consistent with data reported by Mikounou Louya et al [ 40 ]. The yearly co-infection rate showed a significant steady decrease during the study years, which may be related to the decreasing regional detection rate of rotavirus.…”
Section: Discussionsupporting
confidence: 90%
“…Notably, Weishan County hosts one of Northern China's largest freshwater lakes, Weishan Lake, likely in uencing the distribution of RV-A and NV. Additionally, a signi cant number of diarrheal cases involved mixed RV-A and NV GII infections [20,25]. This study identi ed a substantial number of such cases, and their distribution mirrors patterns observed for norovirus and rotavirus in terms of age, month, and county.…”
Section: Evolutionary Tree Analysis Of Nv Gii Genotypessupporting
confidence: 54%
“…Acute diarrheal diseases ranked seventh among the reasons of mortality in LMIC in the international disorder burden collection, 2013, with an envisioned 1. Three million deaths (2 Four %).1 Most of those deaths arise in kids under the age of 5 years in LMIC and diarrhea stays among the top 5 causes of all deaths among children more youthful than age 5 years, as tabulated in 2013 [11][12][13][14][15][16][17][18][19][20].…”
Section: Acute Diarrheamentioning
confidence: 99%
“…The finding rate of norovirus cases associates definitely with humidity. Co-contamination with rotavirus [19,20], astrovirus, and salmonella both may occur in positive cases. Norovirus infections are discovered to reason greater excessive signs of gastroenteritis in children in comparison with rotavirus, especially after the advent of the rotavirus vaccination duration astrovirus.…”
Section: Bacteriamentioning
confidence: 99%